The challenge of establishing world-class universities - Salmi, Jamil (Washington, D.C. World Bank, 2009)
Governments are becoming increasingly aware of the important contribution that high performance universities make to competitiveness and economic growth. This book explores what are the challenges involved in setting up globally competitive universities, also called "elite", or "flagship" universities.
What does it mean to be a world-class university? -- Paths to transformation -- Implications for the World Bank -- Appendices.
Keywords: Education, Higher -- Economic aspects; Economic development -- Effect of education on; Higher education and state; Education and globalization